Dermoscopic features of cutaneous melanoma are associated with clinical characteristics of patients and tumours and with MC1R genotype. (4th March 2014) - Fargnoli, M.C.; Sera, F.; Suppa, M.; Piccolo, D.; Landi, M.T.; Chiarugi, A.; Pellegrini, C.; Seidenari, S.; Peris, K.
Abstract Background Several algorithms are available for the dermoscopic diagnosis of pigmented skin lesions. The MC1R gene is a key determinant of pigmentation characteristics that are established host‐related melanoma risk factors. Objectives To investigate the association of dermoscopic features of sporadic cutaneous melanomas with clinical characteristics of patients and corresponding tumours and with genetic changes in the MC1R and BRAF genes. Methods A total of 64 dermoscopic images of 62 patients were scored by ABCD rule and modified pattern analysis. Detailed patients' and melanomas' characteristics were collected. Patients were screened for germline MC1R variants and related melanomas for somatic V600 BRAF mutations. Results A lower total dermoscopic score (TDS) was observed in melanomas of patients with red hair (P = 0.019), due to reduced dermoscopic structures (P < 0.0001). Thicker melanomas showed higher TDS values (P = 0.021) due to sharper borders (P < 0.0001) and higher number of colors (P = 0.004). An atypical pigment network was prevalent in superficial spreading melanomas (P = 0.010), in individuals with dark skin (P = 0.043) and hair color (P = 0.001). An atypical vascular pattern was more frequent in nodular (P < 0.0001) and thick (P < 0.0001) melanomas, in individuals with skin type I‐II (P = 0.037), blond or red hair color (P = 0.032) and blue or green eyes (P = 0.014). Melanomas of MC1R R carriers showed lower TDS value (P = 0.037), reduced dermoscopic structures (P = 0.001) and lower prevalence of atypical pigment network (P = 0.001). No differences were identified between BRAF‐mutated or wild‐type melanomas. Conclusions We suggest a phenotypic/MC1R profile for melanoma patients and their tumours. Melanomas of MC1R R carriers show a significant lower TDS value, with reduced dermoscopic structures, and a lower prevalence of an atypical pigment network. Non‐carriers of MC1R R variants develop melanomas dermoscopically characterized by an atypical pigment network which is prevalent in superficial spreading melanomas, in patients with dark complexion and less frequent in red‐haired individuals.